PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM YANG MENYENANGKAN DAN EFEKTIF PADA SISWA SMP NEGERI 8 BUTON - La Jusu; Harni Bitomba; Madi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study was conducted with the aim of designing a learning approach for Islamic Religious Education (PAI) that is not only academically effective but also capable of creating an enjoyable learning atmosphere for students at SMP Negeri 8 Buton. The innovation in this learning model was intended to encourage active student engagement, foster positive perceptions toward PAI, and optimize academic achievement. The method employed was Classroom Action Research (CAR), which was implemented in two cycles. Each cycle consisted of the stages of planning, action implementation, observation, and reflection. The study involved 30 eighth-grade students as the primary subjects. The findings revealed clear and significant impacts across various indicators. In the first cycle, student participation increased sharply from 43.3% in the pre-cycle to 76.7%. Students’ perceptions of the learning process also improved positively, with 93.3% of students reporting that the learning experience became more engaging in the second cycle, up from 76.7% in the first. Academic performance followed a similar upward trend. The average student score rose from 68.2 in the pre-cycle to 82.4 by the end of the second cycle. Furthermore, over 86% of students succeeded in surpassing the Minimum Mastery Criteria (KKM), indicating that the developed learning approach effectively enhanced students’ understanding of PAI material.